2016
DOI: 10.1097/md.0000000000005450
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of papillary thyroid carcinoma in elderly patients after thyroid resection

Abstract: The size of the elderly population and the incidence of papillary thyroid carcinoma (PTC) in this group appear to be rapidly increasing, although published information based on more detailed older age groupings are lacking.This study aimed to determine the clinical features and outcomes of elderly patients in PTC.All consecutive patients who received surgery for PTC in our Department from 1978 to 2014 were included. We compared 3 patient groups: young (<65 years), older (65–75 years), and very old patients (>7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
(29 reference statements)
2
22
1
1
Order By: Relevance
“…In contrast, 105 out of 1116 patients (9.4%) of high-risk PTC died of thyroid carcinoma, and the prognosis of high-risk patients became significantly poorer with advancing age. These findings strongly suggest that advanced age can significantly affect the prognosis of only high-risk patients with PTC, which sharply contrasts with findings of previous studies [5,6]. The reason for this phenomenon remains unknown.…”
Section: Discussioncontrasting
confidence: 95%
“…In contrast, 105 out of 1116 patients (9.4%) of high-risk PTC died of thyroid carcinoma, and the prognosis of high-risk patients became significantly poorer with advancing age. These findings strongly suggest that advanced age can significantly affect the prognosis of only high-risk patients with PTC, which sharply contrasts with findings of previous studies [5,6]. The reason for this phenomenon remains unknown.…”
Section: Discussioncontrasting
confidence: 95%
“…Similar findings were reported by Niemann et al, who described a very aggressive pattern among patients with DTC aged under 25 years old and over 75 years old [32]. The former Authors supported a more aggressive surgical approach in DTC patients, suggesting to perform a lymph node dissection along with TT in all patients over 75 year old, especially if RAI ablation would supposed to be problematic and not administrated in this population [2]. In fact, postoperative RAI therapy is affected by several severe complications among elderly population, such as insomnia, osteoporosis and arrhythmias, and is generally administrated with a lower dose [33,34].…”
Section: Discussionsupporting
confidence: 85%
“…Very old patients have generally more aggressive clinicopathological features such as tumor size, extrathyroidal extension, T status and lymphnodes metastases, probably for the delayed diagnosis [2,14]. Chereau et al described a more aggressive tumor behavior in elderly patients with a higher recurrence rate of lymph node metastasis and a lower disease free survival compared to young patients [2]. In particular, the patients over 75 years old were affected by a 2-fold increased risk of recurrence compared with younger patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study was not a single institution study, but an analysis on patients from the SEER database (1998 to 2012), indicating that patients who underwent various kinds of therapy were enrolled. Chareau et al published a single institution study demonstrating that very old patients (>75 years) showed a significantly poorer prognosis than younger patients, but they also showed that the incidence of high-risk patients was higher in very old patients [16]. We also investigated the prognosis of older patients in this series; however, we found that prognosis became poorer with age (60s, 70s, and 80s) for high-risk patients, but not for low-and intermediate-risk patients (data not shown).…”
Section: Discussionmentioning
confidence: 99%